Effect of Irrigation Intervals and Plastic Mulching On Flower Production of Carnation - Qazi, Imran; Ahmad, Masood; Ali, Hamza; Shahana Jabin; Qazi, Shoaib Ali; Masood, Abdullah; Abdul Basit; Zaib, Shayan; Midrar Ullah (Indus Journal of Bioscience Research, 2024)
Calyx splitting is a physiological disorder that results in poor flower production and vase life in carnation. Several scientific reports and literature suggests that this physiological die back and curly tip of carnation flowers might be due to the water stress and potassium deficiency. Keeping in view these facts a field experiment was carried out to study the effect of irrigation intervals and plastic mulching on flower production and control of calyx split in carnation at Ornamental Horticulture Nursery, The University of Agriculture Peshawar, in 2020. Randomized Complete Block Design with a split plot arrangement having two factors was used. Treatments were repeated three times. The plants of carnation were irrigated at different interval (3, 6, 9 and 12 days) allotted to main plots and plastic mulches (transparent, black and green and control / no mulching) were assigned to subplots. Data pertaining to irrigation intervals revealed that least days to flowering (89.7), least calyx splitting (6.1%) and maximum vase life (11.33 days) were recorded in plants irrigated with 12 days’ interval that were statistically similar to the effect of irrigation at 9 days of interval. Findings regarding plastic mulches showed that maximum chlorophyll content (62.8 SPAD), days to flowering (100.5), dry flower weight (2.4g) and vase life (10.95 days) with minimum calyx splitting (7.4%) were recorded in carnation plants of plots covered with green plastic mulch that were statistically similar to the effect of black and transparent plastic mulches. It is concluded that irrigation intervals of 9 and 12 days resulted in early flowering, least calyx splitting and extended vase life. While use of plastic (Transparent, black or green) as mulching material proved superior as compared to control/ no mulching.